Heterogeneity of oral isolates of Candida albicans in HIV-positive patients: correlation between candidal carriage, karyotype and disease stage - CAPOLUONGO, E; MORETTO, D; GIGLIO, A; BELARDI, M; PRIGNANO, G; CRESCIMBENI, E; CORDIALI-FEI, P; MAINI, A; DI CARLO, A; MERCANTINI, R; GIANNETTI, A; AMEGLIO, F (Journal of medical microbiology, 2000)
Laboratory of Microbiology, *Laboratory of Clinical Pathology, Center for Sexually Transmitted Diseases, Scientific Director of the Istituto S. Gallicano, Roma, Italy and Clinica Dermatologica of the University of Modena, Modena, Italy Corresponding author: Dr F. Ameglio (e-mail: ameglioatcrs.ifo.it ). Received 14 Oct. 1999; revised version received 29 March 2000; Paccepted 29 March 2000. Abstract Opportunist infections involving Candida albicans often develop in HIV-positive patients and oral lesions tend to become more frequent as the disease progresses. Previous studies have shown contrasting results concerning the variability of the pulsed-field gel electrophoresis (PFGE) subtypes of C. albicans observed in HIV-positive patients. Carriage of C. albicans was determined by an oral rinse technique; 41 strains of C. albicans (78% serotype A and 22% serotype B) were isolated. There was a direct correlation between candidal load (cfu/ml) and the blood HIV load, whereas there was an inverse correlation with the stage of disease and the CD4 cell counts. The PFGE patterns of isolates were variable with regard to the number and positions of bands. The variability of the band sizes in some run positions showed a Gaussian distribution. Generally, the most frequent size variants were associated with the strains with the highest cfu/ml and lowest CD4 counts ( 200 cells/µl). These findings suggest a possible strain selection over time during disease progression, especially in HIV-positive subjects with low CD4 counts.